Suprachiasmatic VIP neurons are required for normal circadian rhythmicity and comprised of molecularly distinct subpopulations - William D. Todd (Nature Portfolio, 2020)
Cell groups in the hypothalamic suprachiasmatic clock contribute to the genesis of circadian rhythms. The authors identified two populations of vasoactive intestinal polypeptide-expressing neurons in the suprachiasmatic nucleus which regulate locomotor circadian rhythm in mice.